Ispring: The Needs of Teachers and Students toward the ICT-Based Evaluation Tool - Wulandari, Ayu; Alwi, Zahra; Ernalida, Ernalida (LPPM Undiksha, 2022)
An educator requires a learning evaluation tool as the assessment instrument. It can be printed or assisted with the information and communication technology. This qualitative research describes the learners and Indonesian language teachers’ needs toward ICT-based evaluation development for the tenth-grade students. The subjects were taken by purposive sampling based on the objectives and the research needs. They were 68 respondents and three Indonesian language teachers. This research used questionnaire and interview to collect the data. The obtained data were described by the researchers. Based on the findings, the students were already habituated to use ICT-based application. Thus, it indicated their needs of a better, multi-purpose, and multi-utility application so that the researcher recommended Ispring as the evaluation tool for the students. It is a multi-utility authoring e-learning to create various e-learning content types. It has some features to make interesting learning media and to promote presentation. It could be also combined with MS. PowerPoint and can be used to present, support electronic learning, distribute file, and create quizzes.